2023
DOI: 10.1021/acs.jafc.2c06410
|View full text |Cite
|
Sign up to set email alerts
|

New Hydrolase from Aeromicrobium sp. HA for the Biodegradation of Zearalenone: Identification, Mechanism, and Application

Abstract: Zearalenone (ZEN) is an estrogenic mycotoxin most frequently found in cereals that can cause reproductive disorders in livestock and pose a severe threat to animal husbandry. In this study, we isolated a ZEN-degrading Aeromicrobium strain from soil and found that ZenH, a hydrolase, is responsible for the hydrolysis of ZEN through comparative proteomics and biochemical studies. ZenH exhibited the highest similarity with lactone hydrolase ZHD607 from Phialophora americana at 21.52%. ZenH displayed maximal enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…ZEN was detected using an FLD detector at 236 nm. 25 The mobile phase comprised A (water) and B (methanol) at a ratio of 20:80 (v/v). DON was detected at 218 nm, with the mobile phase comprising A (water) and B (methanol) in a ratio of 70:30 (v/v).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZEN was detected using an FLD detector at 236 nm. 25 The mobile phase comprised A (water) and B (methanol) at a ratio of 20:80 (v/v). DON was detected at 218 nm, with the mobile phase comprising A (water) and B (methanol) in a ratio of 70:30 (v/v).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The verified plasmid was transformed into E. coli BL21 (DE3). 25 Transformant E. coli BL21 (DE3) harboring the recombinant vector were chosen based on positive outcomes and then grown in LB liquid medium plus 50 μg/mL kanamycin. Cultures were incubated at 220g at 37 °C until the optical density at 600 nm reached 0.6−0.8.…”
Section: Identification Of Toxin Degradation Productsmentioning
confidence: 99%
“…The cells were washed with 20 mM phosphoric acid buffer (pH 7.5), broken with an ultrasonic homogenizer (Scientz, Ningbo, China) on ice (power of 30%, broken for 1 s, spaced for 3 s, a total of 15 min), and centrifuged for 20 min at 8000 × g to acquire the supernatant. Protein was purified and desalinated using a 5 mL Ni-HisTrap column and a HisTrap desalting column (GE Healthcare, Shanghai, China) . Equilibration buffer (20 mM Tris and 150 mM NaCl, pH 8.0) and elution buffer (20 mM Tris, 150 mM NaCl, and 1 M imidazole, pH 8.0) were prepared.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Protein was purified and desalinated using a 5 mL Ni-HisTrap column and a HisTrap desalting column (GE Healthcare, Shanghai, China). 21 Equilibration buffer (20 mM Tris and 150 mM NaCl, pH 8.0) and elution buffer (20 mM Tris, 150 mM NaCl, and 1 M imidazole, pH 8.0) were prepared. After the protein binds to the column, the impurities are removed with a solution containing 5% elution buffer, and the recombinant protein is eluted with a solution containing 15% elution buffer.…”
Section: Sequence Analysismentioning
confidence: 99%
“…For example, the Aeromicrobium sp. HA, isolated from soil by Hu et al, was found to completely degrade ZEN within three days . Through comparative proteomics and biochemical investigations, a novel ZEN hydrolase (ZenH) was identified.…”
Section: Introductionmentioning
confidence: 99%